The Effect of Board Game on Students’ Vocabulary and Grammar Mastery in Senior High School - Vera Nova Sitanggang; Sahlan Tampubolon; Erika Sinambela (Institut Agama Islam Negeri Palopo, 2023)
This research was conducted based on some problems in learning English especially in vocabulary and grammar. It was also aimed to find out students’ vocabulary and grammar who are taught by using Board GameTechnique and students’ vocabulary and grammar who are taught without using Board Games and find out whether there was any significant effect of using Board Game on the tenth-grade students’ ability in vocabulary and grammar at SMA Kristen Immanuel. In this quasi-experimental design research, the researcher took two of 2 classes as the sample, the experimental class with 20 students in it, and the control class with 20 students as well. The research method was pre-test and post-test of the experimental research. The data collection technique was pre-test and post-test score result. The data were analyzed by using compare means paired sample T-test by comparing the result of pre-test and post-test design, and t-test to know the significant effect in students’ English vocabulary mastery after using Board Game. The result showed there was a significant different between pretest and post test mean. Ho was rejected because significance level was < 0.05. Therefore, there was a significant effect of using board game towards students’ vocabulary mastery of the research. The research of data analysis showed that there was a positive effect of using Board Games on students’ vocabulary and grammar. In which in vocabulary, the t-obtained had a higher value than the t-table either at 5% or 1% significance levels (1,68595 < 4,174> 2,42857). Therefore, Ho is rejected and Ha is accepted; or there is a significant difference in using Board Games on student’s vocabulary and grammar ability of tenth grade students. The result of grammar, the condition of the experimental class was getting better. The students were more active in English learning process. In summing up it may be stated that using Board Game can effect the students‟ grammar mastery and students learning activities at the tenth grader of SMA Kristen Immanuel Medan.